Quality Leadership of Administrator and Cultural Performance in School Under Prachuapkhirikhan Primary Educational Service Area Office 2 - Panmungmee, Chinnawat (Arts of Management Journal, 2020)
The purpose of this study was to study the relationship between quality leadership of administrator and cultural performance in school under Prachuapkhirikhan Primary Educational Service Area Office 2. The sample group used in the study was 73 places under the Prachuap Khiri Khan Primary Education Service Area Office 2, and 2 informants each providing information for each school consisting of the school director or the deputy director of the school or government officials. 1 person and 1 teacher who taught in subjects related to art and culture, a total of 146 informants. The research instrument was a questionnaire about the Quality Leadership of Administrator the executives according to the concept of Sergiovanni and Cultural Performance in school use the manual of the cultural center network in the educational institutions Ministry of Culture. The statistics used for data analysis were frequency, percentage, mean, arithmetic mean, Standard deviation and the Pearson’s product-moment correlation coefficient analysis. The research results were as follows: 1. The qualitative leadership of executives under the Prachuap Khiri Khan Primary Education Service Area Office 2, in overall, the highest level When considered in each aspect at the highest level, 4 aspects and in 4 levels, in order of the highest arithmetic mean, as follows: The purpose was to have a tenure principle, basic necessity. governing principles personnel management, working principles, foresight, and sequential planning Cultural operations in educational institutions under the Prachuap Khiri Khan Primary Education Service Area Office 2, in general, it was at a high level when considered in each aspect, at the high level in all aspects in order by the arithmetic mean of descending as follows: cultural conservation, cultural revival, cultural development, cultural promotion, cultural enhancement work, cultural transfer event respectively, and cultural exchanges. The qualitative leadership of administrators and cultural Operations in schools under the Prachuap Khiri Khan Primary Education Service Area Office 2, in general, there was a moderate level of relationship. Statistically significant at 0.01 level.